Baseline and follow‐up association of the MAX‐PC in Men with newly diagnosed prostate cancer. Issue 4 (21st June 2014) - Tavlarides, Andrea M.; Ames, Steven C.; Thiel, David D.; Diehl, Nancy N.; Parker, Alexander S.
Abstract Objective The objective of this paper is to conduct a prospective, longitudinal study employing the Memorial Anxiety Scale for Prostate Cancer (MAX‐PC) to examine the baseline and follow‐up association of prostate cancer (PCa)‐specific anxiety, health‐related quality of life (HRQOL), and PCa aggressiveness in men with newly‐diagnosed PCa undergoing prostatectomy at our institution. Methods From our prospective PCa registry, we identified a total of 350 men with newly‐diagnosed PCa who completed the MAX‐PC and the Expanded Prostate Cancer Index Composite (EPIC) at baseline and one‐year following surgery. Scores on both measures were compared with clinical measure and demographics using the Wilcoxon Rank Sum, Fisher's exact, and Cochran‐Armitage Trend tests. Spearman test was used to assess correlation at between the MAX‐PC and EPIC at baseline and one‐year. Results Baseline overall MAX‐PC measures were correlated with measures at one‐year (r = 0.5479, p < 0.001). Those reporting high anxiety at one‐year were more likely to have Gleason score > 6 (p = 0.004), T‐Stage ≥ 2C disease (p = 0.004), and a postoperative prostate‐specific antigen (PSA) > 0.1 (p = 0.002); however, this did not apply to all anxious patients. Baseline EPIC sexual function scores were predictive of follow‐up EPIC sexual function scores as well (r = 0.5790, p < 0.001). Depression was noted as a problem in 16% of patients at follow‐up. Conclusions Our data suggests that the MAX‐PC could be used at baseline as a tool to determine who may benefit from psychological intervention pre‐PCa and post‐PCa treatment. In terms of individualized medicine, behavioral therapy may be the most beneficial in improving HRQOL for younger patients, those with advanced stage disease, and more specifically those whose anxiety outweighs their actual prognosis. Copyright © 2014 John Wiley & Sons, Ltd.